Open science and human genetic data: recommendations on South Africa’s Draft National Open Science Policy - Thaldar, Donrich; Gooden, Amy; Steytler, Michaela (Frontiers in Genetics, 2023)
The Draft National Open Science Policy, which was shared by the South African government with stakeholders in 2022, is an encouraging step forward as it aims to promote the practice of open science in South Africa through a system of incentives. Since South Africa is constitutionally committed to be an open and democratic society, this approach is preferable to the approach of state control that characterizes the Draft National Policy on Data and Cloud-another data-related policy initiative by the South African government. However, there is room for improvement in the Draft National Open Science Policy. In particular, it should (a) rely on the right to freedom of scientific research to strengthen the policy; (b) rectify the omission of ownership from its policy analysis; and (c) retain a clear differentiation between human and non-human genetic data. This will ensure that the final policy is clearly anchored in the South African Constitution, and that the principle of "as open as possible, as closed as necessary" can be applied to human genetic data in a legally well informed and accountable way.